خەندەکەى بایی – دڵدار و گۆمى – لامارتین - محمد, محمد دلێر ئەمین; محمد, هیدایەت عبد اللە (Sulaimani Journal for Humanities, 2007)
This comparative study is about tow poems : THE LAKE of french poet de Lamartin (1790-1869) and his poems influence of the kurdish poem THE SMILE OF COQUETTE which written by the kurdish poet Dildar (1918-1948) we tried to show the points of connection , similary and differences between their poems by analyzing them in the poetic and linguistic aspects and plan.